Recurrent Atypical Meningioma with Pleural Metastases - Premraj, Sarah; Muniraj, Femela; Riaz, Juhi; Senthilnayagam, Balamurugan (Indian Journal of Medical and Paediatric Oncology, 2018)
Meningiomas are the most common primary intracranial tumors in adults. Although Grade I meningiomas are considered benign, Grade II/III (atypical and anaplastic) meningiomas are known to be locally aggressive, recurrent, and rarely present with distant metastases. We report a 40-year-old female with recurrent atypical meningioma (WHO Grade II) who presented with features suggestive of a massive right-sided pleural effusion. Imaging showed bilateral large pleural-based lesions, and histopathological examination and immunohistochemistry of the mass were consistent with metastatic atypical meningioma. A high index of suspicion is warranted to detect extracranial metastases, especially in patients with recurrent meningiomas and higher WHO grade of tumor.
Keywords: Atypical meningioma; extracranial metastasis; pleural metastasis; recurrent